20 years trend in office environment: bibliometric analysis and future research agenda / Masliza Mohd Razali … [et al.] - Mohd Razali, Masliza; Bashirun, Siti Norashikin; Ahmad, Siti Nurul Akma; Jamian, Nur Faithzah; Eshak, Erratul Shela (2023)
This paper runs a bibliometric analysis to present the characteristics and evolution of the publications of the research on office environment. Our sample is composed of all the 152 documents from the SCOPUS for the period 2000-2022. The findings show that office environment research activity has been fluctuating for the past 22 years. The analysis also reveals the most cited authors and papers, including the most frequent topics in this research area, highlighting that current trends are moving toward green office, employee well-being and work from home. Potential research directions are also provided by suggesting specific research themes and conceptual approaches. This comprehensive exploration has provided valuable insights into the concept of office environment, its objectives, and its potential benefits for future research.